Subsurface Power: How Mineral Rights are Hidden and How to Uncover Them - Ford, Sophia (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
Mineral rights, and more generally, the land below the surface, are legally classified as real property and sold separately from surface property. The vertical separation of property rights, coupled with intricate procedures for accessing property information, poses complex challenges for people seeking to safeguard their communities, including activists, Indigenous communities, homeowners, environmental organizations, and local communities. Drawing from the conceptual framework of administrative burdens, as defined by Herd and Moynihan (2018), I argue that these deliberate opacities and complex bureaucratic obstacles create significant challenges for individuals seeking government goods and services. In this context, I identify the key legal, bureaucratic, spatial, and cost barriers to uncovering subsurface property details as well as the methods that facilitate the identification of mineral claimants, two pieces of knowledge that can enable the exercise of Indigenous sovereignty and offer a countermeasure against unbridled mineral extraction. In addition, this paper illustrates how limited accessibility to such information benefits the state and corporations while excluding local communities from decision-making. The identification of mineral claimants brings to light dual power dynamics: one at the surface attempting to access public information that remains elusive, and the other delving deep beneath the Earth's surface, unraveling the holders of mineral claims as a strategic resistance against unchecked extraction.